Investigation of nano-silicon nitride ceramics containing an yttria sintering additive and the carbon thermal reduction reaction. Issue 10 (1st August 2016) - Lu, Horng-Hwa; Chen, Ching-Yu
Abstract: Carbothermal reduction treatment (CRT) and spark plasma sintering (SPS) were employed to prepare nano-silicon nitride ceramics from an amorphous silicon nitride powder containing yttria (Y2 O3 ) as an additive, and the effects of the Y2 O3 contents and reducing agent additives on the ceramic densification and phase transformation behavior were examined. The results showed that specimens with 6 wt% Y2 O3 generated dense sintered bodies with sufficient liquid-phase contents. Specimens with 3 wt% and 4 wt% carbon black produced single-phase silicon nitride after the CRT and SPS processes. In addition, increasing the quantity of carbon black enabled the effective removal of the second phase of silicon oxynitride and allowed the grain size of the sintered body to be maintained at a nanoscale level. An excess of the carbon black additive resulted in insufficient liquid phase production, hindering the complete conversion of α-phase silicon nitride into β-phase silicon nitride, which in turn affects the density of the sintered bodies.